Circadian Mechanisms: Cardiac Ion Channel Remodeling and Arrhythmias - Bernardi, Joyce; Aromolaran, Kelly A.; Zhu, Hua; Aromolaran, Ademuyiwa S. (Frontiers in Physiology, 2021)
Circadian rhythms are involved in many physiological and pathological processes in different tissues, including the heart. Circadian rhythms play a critical role in adverse cardiac function with implications for heart failure and sudden cardiac death, highlighting a significant contribution of circadian mechanisms to normal sinus rhythm in health and disease. Cardiac arrhythmias are a leading cause of morbidity and mortality in patients with heart failure and likely cause ∼250,000 deaths annually in the United States alone; however, the molecular mechanisms are poorly understood. This suggests the need to improve our current understanding of the underlying molecular mechanisms that increase vulnerability to arrhythmias. Obesity and its associated pathologies, including diabetes, have emerged as dangerous disease conditions that predispose to adverse cardiac electrical remodeling leading to fatal arrhythmias. The increasing epidemic of obesity and diabetes suggests vulnerability to arrhythmias will remain high in patients. An important objective would be to identify novel and unappreciated cellular mechanisms or signaling pathways that modulate obesity and/or diabetes. In this review we discuss circadian rhythms control of metabolic and environmental cues, cardiac ion channels, and mechanisms that predispose to supraventricular and ventricular arrhythmias including hormonal signaling and the autonomic nervous system, and how understanding their functional interplay may help to inform the development and optimization of effective clinical and therapeutic interventions with implications for chronotherapy.